Pengembangan Media Pembelajaran Multimedia untuk Meningkatkan Hasil Belajar dalam Memahami Pengoperasian Aplikasi Autodesk Inventor - Herlambang, Doni; Khumaedi, Muhammad; Musyono, Ari Dwi Nur Indriawan; Huda, Khoirul (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Autodesk Inventor software learning in manufacturing drawing subjects in vocational schools requires the support of interactive visual-based media to make complex technical materials easier for students to understand. The weakness of conventional methods in conveying this concept requires a breakthrough through the use of modern learning technology. This study focuses on evaluating the effectiveness of using PowerPoint-based multimedia to improve students' mastery of Autodesk Inventor. The research design used the purposive sampling method with pre-test and post-test models in two groups involving 60 students in grade XI of Mechanical Engineering at SMK Negeri 5 Semarang. The experimental group made use of interactive PowerPoint media, while the control group continued to use traditional methods. The results showed a significant increase in the experimental group with a p< value of 0.05 and an N-Gain value of 0.499 much higher than the control group with only 0.148. Thus, the use of interactive PowerPoint has proven to be effective in strengthening students' understanding of assembly engineering materials in a more interesting, flexible, and appropriate way for learning needs.